(untitled) (INTERNATIONAL SCIENTIFIC INNOVATION RESEARCH CONFERENCE, 2024)
Interactive methods for teaching English have revolutionized language education by fostering greater student engagement and enhancing the effectiveness of learning. This annotation outlines several key interactive teaching methods, detailing their descriptions and practical applications in the classroom